Pengembangan Media Pembelajaran Booklet Berbasis Contextual Teaching and Learning terhadap Kemampuan Berpikir Kritis Matematis Siswa Di SMP Negeri 1 Sirombu - Zebua, Kasihani; Mendrofa, Netti Kariani (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2023)
Based on preliminary studies conducted at SMP Negeri 1 Sirombu, it was found that students' mathematical critical thinking abilities are relatively low. The solution to this issue is to use booklet-based learning media in the teaching process. This research aims to develop a Contextual Teaching and Learning-based booklet learning media that is valid, practical, and effective in improving students' mathematical critical thinking abilities. This study is a development research. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in this research are validation questionnaires, response questionnaires, and tests of students' mathematical critical thinking abilities. Based on the research results, the developed booklet learning media has been validated by subject matter experts, language experts, and design experts, with an average validity percentage of 94.48%, indicating a very valid criterion. Furthermore, the booklet learning media is highly practical for students and teachers, with an average practicality percentage of 95.88%. The booklet learning media is also effective, with an average effectiveness percentage of 73%, indicating a moderate criterion.